The Nature of Allah in the Perspective of Shia, Mu'tazilah and Ahlussunnah Wal Jama'ah - Mansur, Safiin; Taqiyuddin, Hafidz (Jurusan Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2024)
This research aims to find out more about the attributes of God and their division in terms of similarities and differences between Shia, Mu'tazilah and Ahlus Sunnah Wal Jama'ah. These three schools recognize that God has properties based on God's revelation, such as qudrat, hayat, iradah, bashar, sama, qadim, wujud, and kalam. The division of God's attributes is based on reason. Although there are differences, they do not interfere with the basis of Islamic faith, such as Mu'tazilah rejecting the existence of God's attributes but recognizing the existence of God's Substance and its division. Shia divides the nature of God into two things: the nature of Tsubutiyah and Salbiya. Mu'tazilah has three properties of God's Substance, namely the Fi'li nature of God, the nature of God's Substance, and God's Body. Ahlus Sunnah Wal Jama'ah has three attributes: obligatory nature, impossible nature, and Jaiz nature of God. The difference is used as knowledge and God's mercy and should not fade the unity of Islam.